Cloud computing: Analysis of various services - Khan, Nawsher; Noraziah, Ahmad; Herawan, Tutut; Mustafa, Mat Deris (Springer, Berlin, Heidelberg, 2012)
Cloud computing fulfills the long-held dream of computing as a utility and fundamentally altering the expectations for how and when computing, storage and networking resources should be allocate, managed, consume and allow user to utilize services globally. Due to the powerful computing and storage, high availability and security, easy accessibility and adaptability, reliable scalability and interoperability, cost and time effective, cloud computing is the top needed for current fast growing business world. A client, organization or a trade that adopting emerging cloud environment can choose a well suitable infrastructure, platform, software and a network resource, for any business, where each one has some exclusive features and advantages. In this paper, we first present a comprehensive classification for describing cloud computing architectures. This classification help in survey of several existing cloud computing services developed by various projects globally such as Amazon, Google, Microsoft, Sun and Force.com. Then by using this survey results, we identify similarities and differences of the architecture approaches of cloud computing.